Risk sharing and public transfers - Stefan Dercon; Pramila Krishnan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
We use public transfers in the form of food aid to test for the presence of risk sharing arrangements at the village level in rural Ethiopia. We reject perfect risk-sharing, but find evidence of partial risk-sharing via transfers. There is also evidence consistent with crowding out of informal insurance linked to food aid programmes. – risk ; public transfers ; informal insurance
Keywords: E20; I38; O17; 330; Öffentlicher Transfer; Nahrungsmittelhilfe; Risiko; Ländlicher Raum; Äthiopien